The Kingdom of Eswatini Toward Equal Opportunity : Accelerating Inclusion and Poverty Reduction - World Bank (World Bank, Washington, DC, 2021)
One of three kingdoms in Africa, the Kingdom of Eswatini (formerly Swaziland) is a small, homogeneous, and landlocked country that is quasi-enclaved within South Africa. Eswatini is one of the world’s most trade-dependent economies, with South Africa as its most important trading partner. The COVID-19 pandemic is expected to worsen Eswatini’s growth outlook in the near to medium term, which will exacerbate the triple problems of high unemployment, poverty, and inequality. Eswatini has high levels of poverty and income inequality, which are not commensurate with its middle-income status. This Systematic Country Diagnostic views addressing inequality of opportunity, manifested in people’s unequal access to assets, markets, services, and rights, as central to accelerating poverty reduction and shared prosperity in Eswatini. To this end, it identifies five interconnected, broad priority policy areas that could potentially make the greatest contribution to eliminating extreme poverty and boosting shared prosperity. These are: (a) strengthening macroeconomic management; (b) diversifying the economy and creating jobs; (c) strengthening human capital and the inclusive delivery of public services; (d) improving resilience to natural disasters and economic shocks; and across these four areas, (e) demonstrating credible commitment to transparent and effective policy implementation.